2002
DOI: 10.1067/mcp.2002.122471
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epinephrine compared with the combination of dobutamine and norepinephrine on gastric perfusion in septic shock

Abstract: In patients with septic shock, at doses that induced the same mean arterial pressure, epinephrine enhanced more gastric mucosal blood flow than the combination of dobutamine at 5 microg/kg per minute and norepinephrine. This effect was probably a result of higher cardiac index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 14 publications
1
37
1
Order By: Relevance
“…The role of epinephrine in patients with septic shock is unclear. Although studies such as those by Seguin et al 51 and Levy et al 52 have shown a difference in hemodynamic parameters and measures of tissue perfusion, two RCTs comparing norepinephrine (+ dobutamine where indicated) to epinephrine did not show a difference in mortality. 20,53 The 2012 Surviving Sepsis Guidelines recommend the addition of epinephrine to norepinephrine "when [an] additional agent is needed to maintain adequate blood pressure".…”
Section: Question 5: Which Vasopressors and Inotropes Should Be Used mentioning
confidence: 99%
See 1 more Smart Citation
“…The role of epinephrine in patients with septic shock is unclear. Although studies such as those by Seguin et al 51 and Levy et al 52 have shown a difference in hemodynamic parameters and measures of tissue perfusion, two RCTs comparing norepinephrine (+ dobutamine where indicated) to epinephrine did not show a difference in mortality. 20,53 The 2012 Surviving Sepsis Guidelines recommend the addition of epinephrine to norepinephrine "when [an] additional agent is needed to maintain adequate blood pressure".…”
Section: Question 5: Which Vasopressors and Inotropes Should Be Used mentioning
confidence: 99%
“…68 Earlier studies demonstrated that dobutamine improved cardiac index as well as creatinine clearance and gastric microcirculation. 51,69,70 More recent studies on the use of dobutamine in septic shock also demonstrated an improvement in cardiovascular parameters, but only limited improvement in microcirculation. [71][72][73] Dobutamine was included in Rivers' study of early goal directed therapy.…”
mentioning
confidence: 99%
“…) has demonstrated beneficial effects in the treatment of septic shock, including improvements in MAP, CI, SVR, oxygen delivery, and gastric mucosal blood flow without detrimental effects on oxygen consumption or lactate levels (40,50). The above studies suggest that there are dose-dependent harmful effects of epinephrine on organ perfusion in humans consistent with the dose-dependent impairment of systemic perfusion and endorgan injury seen in our canine study.…”
mentioning
confidence: 99%
“…Clinical studies yielded conflicting results with respect to the effect of dobutamine on left ventricular stroke work index, mean arterial pressure and mean pulmonary artery pressure (29)(30)(31)(32)(33) (14). Other studies also failed to draw a definitive conclusion (15,(23)(24)(25).…”
Section: Dobutaminementioning
confidence: 87%
“…It is less commonly used as the first line therapy for septic shock. But there are still many investigations on the effectiveness of epinephrine (14,15,(22)(23)(24)(25)(26). Subjects in these trials were randomized to receive either epinephrine alone or norepinephrine plus dobutamine, because norepinephrine has only moderate effect on the cardiac β1 receptor.…”
Section: Dopamine and Norepinephrinementioning
confidence: 99%